Electrosynthesized MoS2 Thin Films for Photoelectrochemical (PEC) Cells - T., Joseph Sahaya Anand; S., Shariza; Z.M., Rosli (Malaysian Association of Solid State Science (MASS), 2012)
Transition metal dichalcogenides, MoSxSe2-x is a layered compound, which is widely used in photovoltaic applications together with other similar binary compound materials (MoS2, MoSe2, WS2, WSe2, etc.,). MoSxSe2-x, films were cathodically deposited by electrosynthesis process. These films were prepared on conducting tin oxide coated glass substrates as well as titanium substrates. By changing the deposition parameters like bath temperature, pH of the bath, concentration of the solution, deposition time etc. will yield device quality films. Deposition potential was in the range of -450 to -750 mV, which was derived from cyclic voltammograms. pH of the bath was maintained at 9.2 ± 0.1. The prepared films were characterized by X-ray diffraction analysis to study its structural characterization. The X-ray diffraction studies reveal that the films are polycrystalline nature with hexagonal structure. A Mott-Schottky plot was drawn to find out the semiconductor parameters. From the plot, the type of the film was found to be n-type. From the optical studies, the energy gap value was calculated as 1.68 eV and they possess indirect nature.